Palliative Care for Stroke Patients and Their Families: Barriers for Implementation - Steigleder, Tobias; Kollmar, Rainer; Ostgathe, Christoph (Frontiers in Neurology, 2019)
Stroke is a leading cause of death, disability and symptom burden worldwide afflicting both patients and families in various dimensions comprising physical, emotional, social and existential aspects. Thereby stroke qualifies as eligible for palliative care (PC) support in accordance with the contemporary definition of PC published by the WHO in 2002 and reflected throughout many entities. Core competencies of PC comprise critical appraisal of various treatment options and discussing therapeutic goals openly and respectfully with patients, families and caregivers; furthermore a structured approach to palliative care needs and amelioration of symptom burden is essential. Nevertheless PC in stroke is to date mainly restricted to care for dying patients in life limiting complications of acute stroke. An approach when to initiate PC for stroke patients and which symptoms to screen for as well as an integrated concept for PC in stroke care are lacking. Hence, PC for stroke patients is currently rather an emergency solution and retains the association with death and dying. Instead PC as an integrated approach to holistic stroke care is to focus on quality of life and living. We identified key aspects of PC in stroke care and current barriers to implementation.